صفات مورفولوجية وتشريحية لنوعين من جنس ذنب القط .Typha L من فصيلة Typhaceae ينتشران في بعض مناطق اللاذقية- سوريا - ديبو, سلمى (Latakia University Journal -Biological Sciences Series, 2018)
At this study, two species of genus Typha L. have been recorded, that they were: Typha domingensis Pers. and Typha angustifolia L. The two species we recorded for the first time in Lattakia. The morphological features were used to separate two species (measurement the spikes flowers and shapes, number of the hairs at the ovary, existence the bracteoles or absence, number of stamens and measurements, shapes of the scales and measurements). This study showed that: the pollen grains of the two species, they were very similarity, the pollen grains were rounded and they had an aperture. Also showed obvious difference in measurements the spikes male and female and difference in their shapes. تمّ جمع نوعين من جنس ذنب القط Typha L. في هذه الدراسة وهما : النوع T.domingensis Pers والنوع ذنب القط ذو الأوراق الضيقة T.angustifolia L. تمّ تسجيل النوعين المدروسين لأول مرة في اللاذقية . تمّ تمييز النوعين عن بعضهما بالإعتماد على الصفات المورفولوجية ( أبعاد السنابل الزهرية وأشكالها، عدد أشعار المبيض وأبعادها، وجود القنّابات أو غيابها، عدد الأسدية وأبعادها، أشكال الحراشف وأبعادها). أوضحت الدراسة وجود تشابه كبير في أشكال حبات الطلع التي تميزت بشكلها الكروي مع وجود فتحة إنتاش وحيدة. كما لوحظ اختلاف واضح في أبعاد السنابل الزهرية المذكرة والمؤنثة وأشكالها.